Positive pre-breakdown streamer propagation and breakdown voltage of palm oil based Al2O3 - Thien, Yee Von; Azis, Norhafiz; Mohamad, Nur Aqilah; Tan, Xiao Jian; Yaakub, Zaini (IEEE, 2023)
This research paper presents the experimental results of the lightning pre-breakdown and breakdown voltages of Palm Oil (PO) and Mineral Oil (MO) in the presence of Al2O3 under positive voltage polarity. The experiments were conducted using a needle-plane electrode configuration as a non-uniform field. The positive lightning breakdown voltages of two types of refined, bleached, and deodorized PO with various concentrations of nanofluids were determined. The lightning pre-breakdown was monitored through light signal recordings. The light signal emission increased with the applied voltage for all samples. The presence of Al2O3 in both PO and MO increases the positive lightning breakdown voltages.